2013
DOI: 10.1093/europace/eus376
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac resynchronization therapy improves ejection fraction and cardiac remodelling regardless of patients' age

Abstract: Cardiac resynchronization therapy is as effective in improving LVEF in elderly as in non-elderly patients. Age alone should not be a determinant to restrict resynchronization therapy in HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
2
15
0
3
Order By: Relevance
“…Thirdly, our results showed that neither EF nor mitral regurgitation could differ entiate between responders and non-responders to CRT. These commonly used two parameters of LV function in HF patients have been shown to improve with CRT in many studies (6,7), We concur with those, having demonstrated a significant increase in EF in the group of patients as a whole and a fall in mitral regurgitation with CRT, despite the failure of the two measures to discriminate between groups. Again, this finding was not unexpected since the two measures reflect overall systolic LV function and degree of mitral valve dysfunction rather than the nature and severity of LV dyssynchrony which is the main objective target of CRT electrical treatment.…”
Section: Data Interpretationsupporting
confidence: 81%
See 2 more Smart Citations
“…Thirdly, our results showed that neither EF nor mitral regurgitation could differ entiate between responders and non-responders to CRT. These commonly used two parameters of LV function in HF patients have been shown to improve with CRT in many studies (6,7), We concur with those, having demonstrated a significant increase in EF in the group of patients as a whole and a fall in mitral regurgitation with CRT, despite the failure of the two measures to discriminate between groups. Again, this finding was not unexpected since the two measures reflect overall systolic LV function and degree of mitral valve dysfunction rather than the nature and severity of LV dyssynchrony which is the main objective target of CRT electrical treatment.…”
Section: Data Interpretationsupporting
confidence: 81%
“…C R T has been shown to improve survival (2)(3) and quality of life (4); reduce the rate of hospitalization (2,3,5); increase E F (6); and reduce m itral regurgitation (7). D espite that, over 30% of patients receiving C R T do n o t respond either sym ptom atically or in cardiac function param eters (6,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonrandomized studies have found similar reversals of left ventricular remodeling for old and young patients after CRT placement (11)(12)(13)(14).…”
Section: In a Substudy Of Then Madit-crt (Multicentermentioning
confidence: 83%
“…The results of studies showing the effect of cardiac resynchronization therapy in elderly patients are contradictory. Some studies [5] do not show differences in mortality in older and younger patients. Other works [6] show that a greater age is a risk factor for higher mortality, together with other data (New York Heart Association functional class IV, impaired renal function, atrial fibrillation, and left ventricular ejection fraction <22%).…”
Section: Predictors Of Response To Cardiac Resynchronization Therapymentioning
confidence: 93%